RESEÑA de: Bueno, Lourdes; Gabriele, John P.; Leonard, Candyce (eds.). Acto seguido: el personaje del teatro español contemporáneo a escena. Wiston-Salem, North Carolina : Teatro, 2012. - Freear-Papio, Helen (Signa: Revista de la Asociación Española de Semiótica, 2014)
-